KARAKTERISTIK AKSEPTOR KB DALAM PEMILIHAN METODE ALAT KONTRASEPSI DI DESA OILIT RAYA KABUPATEN KEPULAUAN TANIMBAR - Sitti Suharni Hermanses; Vina Dwi Wahyunita; Kristiova Masnita Saragih (Poltekkes Kemenkes Maluku, 2022)
The family planning program must consider the issue of gender equality in formulating its priority activities. The choice of using contraceptive methods is influenced by perceptions or previous experiences, knowledge, beliefs, influence factors, social factors and other factors, before making a decision the acceptor seeks information first by considering risk factors, choices and communication. The purpose of this study was to determine the characteristics of family planning acceptors in the selection of contraceptive methods in Olilit Raya village, Tanimbar Islands Regency. The method of this research is descriptive quantitative research with the type of research is retrospective. The study was conducted to determine the characteristics of the respondents, namely age, number of children, JKN participation, desire to have children, age of last child. The population in this study was used as a sample (total sampling), namely all the target family planning acceptors as many as 126 family planning acceptors. The results showed that 73 respondents (57.9%) of family planning acceptors chose to use injectable contraception, 92 respondents (73%) were aged 20-35 years, the highest parity of family planning acceptors was mothers who had multiparous children (90.5%) with the number of children between 2 to 4 people, 102 respondents (81.0%) family planning acceptors have National Health Insurance (JKN), 41 respondents (32.5%) family planning acceptors have children under five, children and adolescents. It is hoped that efforts to increase family planning participation need to be carried out on an ongoing basis with advocacy and KIE/Counseling for family planning services.